The association between chronic heart failure and frailty index: A study based on the National Health and Nutrition Examination Survey from 1999 to 2018 - Chen, Xiaozhe; Hou, Chunlei; Yao, Lei; Ma, Yulong; Li, Yunfeng; Li, Jianhua; Gui, Mingtai; Wang, Mingzhu; Zhou, Xunjie; Lu, Bo; Fu, Deyu (Frontiers in Cardiovascular Medicine, 2023)
Objective This study aims to explore the association between the frailty index and chronic heart failure (CHF). Methods We collected data from the National Health and Nutrition Examination Survey (NHANES) (1998–2018) database to assess the association between CHF and frailty. Demographic, inquiry, laboratory examinations, and characteristics were gathered to compare CHF and non-CHF groups. Multiple logistic regression analysis was performed to explore the relationship between frailty and CHF. Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence interval (CI) for mortality from all causes and cardiovascular disease (CVD). Results A total of 16,175 participants with cardiac and cerebrovascular disease were categorized into CHF (n = 1,125) and non-CHF (n = 15,050) groups. In patients with CHF, the prevalence of frailty, pre-frailty, and non-frailty were 66.31, 30.93, and 2.75%, respectively. In multiple logistic regression, patients with CHF who were male (OR = 0.63, 95% CI: 3.11–5.22), whose annual family income was over 20,000 (OR = 0.52, 95% CI: 0.37–0.72, p < 0.001), or with normal hemoglobin level (OR = 0.77, 95% CI: 0.68–0.88, P < 0.001) had a lower likelihood of frailty. CHF patients with hypertension (OR = 3.60, 95% CI: 2.17–5.99, P < 0.0001), coronary heart disease (OR = 1.76, 95% CI: 1.10–2.84, P = 0.02), diabetes mellitus (OR = 1.89, 95% CI: 1.28–2.78, P < 0.001), and stroke (OR = 2.52, 95% CI: 1.53–4.15, P < 0.001) tended to be frail. Survival analysis suggested that pre-frailty and frailty were related to poor all-cause deaths (HR = 1.48, 95% CI: 1.36–1.66; HR = 2.77, 95% CI: 2.40–3.18) and CVD mortality (HR = 1.58, 95% CI: 1.26–1.97; HR = 2.55, 95% CI: 2.02–3.21). CHF patients with frailty were strongly connected with all-cause death (HR = 2.14, 95% CI: 1.27–3.62). Conclusion Frailty was positively associated with CHF. Patients with CHF who were male, whose annual family income was over 20,000, or with normal hemoglobin level were negatively correlated to frailty. For patients with cardiac and cerebrovascular disease as well as CHF, frailty was strongly connected with all-cause death.